Similarity of adaptogenic effects of bioactive naftussya water and phytocomposition “Balm Truskavets’” - Popovych, Igor L. (Journal of Education, Health and Sport, 2023)
Background. From previous studies, it is known about the adaptogenic properties of Naftussya bioactive water and the Ukrainian phytocomposition "Balm Truskavets’". Both adaptogens have a common component of the composition - polyphenols, which suggests the existence of similar effects on the parameters of the body responsible for adaptation. The purpose of this study is to test the hypothesis. Material and methods. The object of clinical-physiological observation were 30 practically healthy individuals of both sexes with dysfunction of the neuro-endocrine-immune complex as a manifestation of maladaptation. Before and after a one-week course of using Balm (10 people) or Naftussya water (20 people), plasma levels of the main adaptation hormones, parameters of electroencephalogram (EEG), heart rate variability (HRV), phagocytosis, leukocytogram, as well as acupuncture and bioelectrophotonics were recorded. Results. 39 parameters (18 EEGs, 8 HRVs, 5 biophysical, 4 phagocytosis, as well as the Popovych’s leukocytary adaptation index, triiodothyronine, testosterone and cortisol) were identified, the physiologically favorable changes of which are common to both adaptogenic means. Conclusion. The influence of adaptogens of various nature on the state of adaptation of the body is non-specific and is implemented through the neuro-endocrine-immune complex.